Proline and Proline Analogues Improve Development of Mouse Preimplantation Embryos by Protecting Them against Oxidative Stress - Madeleine L. M. Hardy; Dheerja Lakhiani; Michael B. Morris; Margot L. Day (Cells, 2023)
The culture of embryos in the non-essential amino acid L-proline (Pro) or its analogues pipecolic acid (PA) and L-4-thiazolidine carboxylic acid (L4T) improves embryo development, increasing the percentage that develop to the blastocyst stage and hatch. Staining of 2-cell and 4-cell embryos with tetramethylrhodamine methyl ester and 2′,7′-dichlorofluorescein diacetate showed that the culture of embryos in the presence of Pro, or either of these analogues, reduced mitochondrial activity and reactive oxygen species (ROS), respectively, indicating potential mechanisms by which embryo development is improved. Inhibition of the Pro metabolism enzyme, proline oxidase, by tetrahydro-2-furoic-acid prevented these reductions and concomitantly prevented the improved development. The ways in which Pro, PA and L4T reduce mitochondrial activity and ROS appear to differ, despite their structural similarity. Specifically, the results are consistent with Pro reducing ROS by reducing mitochondrial activity while PA and L4T may be acting as ROS scavengers. All three may work to reduce ROS by contributing to the GSH pool. Overall, our results indicate that reduction in mitochondrial activity and oxidative stress are potential mechanisms by which Pro and its analogues act to improve pre-implantation embryo development.